2020
DOI: 10.1111/bcp.14415
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year trend of opioid and nonopioid analgesic use in the French adult population

Abstract: Aims Analgesics are the most widely used medicines worldwide. In parallel, opioid abuse has increased and is of major concern. The accessibility of pharmacologically powerful medicines and the addictovigilance signals in France about the risk of opiates addiction call for an overview of analgesic use. The objective of this study was to investigate the use of analgesics reimbursed in France over a 10‐year period through its prevalence. Methods A cross‐sectional study repeated yearly was conducted by using data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(129 reference statements)
2
14
1
1
Order By: Relevance
“…The study by Daveluy et al observed an increase in analgesic drug use in France from 2006 to 2015, with a higher prevalence in women compared to men all over the period 19 . At the whole adult population level, the annual prevalence of paracetamol use increased from 42.1% in 2006 to 52.6%, which confirms the trends observed in our study on a healthy worker population.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Daveluy et al observed an increase in analgesic drug use in France from 2006 to 2015, with a higher prevalence in women compared to men all over the period 19 . At the whole adult population level, the annual prevalence of paracetamol use increased from 42.1% in 2006 to 52.6%, which confirms the trends observed in our study on a healthy worker population.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study conducted in France regarding the risk of strong opioid PIU in terminally ill cancer patients at the general population level. Fentanyl was the most frequently used strong opioid analgesic in this population, followed by morphine and oxycodone, which is somewhat different from that observed in the general French population, with morphine at the first rank in 2015, followed by oxycodone and fentanyl at the same rank 34 . About 1/3 of cancer patients in the EGB were exposed to strong opioids in their last year of life, which is lower than in other studies 10,11 .…”
Section: Discussioncontrasting
confidence: 67%
“…Groups 2 and 3 showed more notorious increases with 882 and 1,642 cases respectively over the 2008-2020 period. These findings may be explained by the wide availability of acetaminophen contained, as a single drug and in combination with other drugs, in marketed drug products, especially in the most recent years [21][22][23][24]. When including patients' gender, there were statistically significant differences when comparing Group 1 to Group 2…”
Section: Age and Gender Of Poisoned Patientsmentioning
confidence: 99%